Conservative management of a post-traumatic pseudoaneurysm of the artery of cervical enlargement–anterior spinal artery junction. (25th March 2015) - Boeris, Davide; Mortimer, Alex; Sakthithasan, Mathuri; Evins, Alexander Ian; Sandeman, David; Renowden, Shelly
Abstract : A 22-year-old man suffered severe sudden onset head and neck pain after being pushed from behind during an assault. Physical examination was normal. Cervical MRI demonstrated an intradural hematoma, anterior to the cord, between C2–4. Subsequent contrast enhanced MR angiography and digital subtraction vertebral angiography confirmed that the cause of the hemorrhage was a fusiform (presumed dissecting) pseudoaneurysm of the artery of the cervical enlargement at its junction with the anterior spinal artery. The aneurysm was managed conservatively. Follow-up angiography demonstrated that the aneurysm had spontaneously thrombosed within 10 days and remained occluded at 2 months. The patient remained occluded at 6 months following the initial injury. Anterior spinal aneurysms represent a management dilemma and options are discussed.